Effects of phase stability, lattice ordering, and electron density on plastic deformation in cubic TiWN pseudobinary transition-metal nitride alloys. (15th January 2016) - Sangiovanni, D.G.; Hultman, L.; Chirita, V.; Petrov, I.; Greene, J.E.
Abstract: We carry out density functional theory calculations to compare the energetics of layer glide, as well as stress vs. strain curves, for cubic Ti0.5 W0.5 N pseudobinary alloys and reference B1-structure TiN. Irrespective of the degree of ordering on the metal sublattice, the hardness and stiffness of Ti0.5 W0.5 N, as estimated by stress–strain results and resistance to layer glide, are comparable to that of the parent binary TiN, while ductility is considerably enhanced. After an initial elastic response to an applied load, the pseudobinary alloy deforms plastically, thus releasing accumulated mechanical stress. In contrast, stress continues to increase linearly with strain in TiN. Layer glide in Ti0.5 W0.5 N is promoted by a high valence-electron concentration which enables the formation of strong metallic bonds within the slip direction upon deformation. [111]-oriented Ti0.5 W0.5 N layers characterized by high local metal-sublattice ordering exhibit low resistance to slip along <110> directions due to energetically favored formation of (111) hexagonal stacking faults. This is consistent with the positive formation energy of <111>-ordered Ti0.5 W0.5 N with respect to mixing of cubic-B1 TiN and hexagonal WC-structure WN. In the cubic pseudobinary alloy, slip occurs parallel, as well as orthogonal, to the resolved applied stress at the interface between layers with the lowest friction. We suggest that analogous structural metastability (mixing cubic and hexagonal TM nitride binary phases) and electronic (high valence electron concentration) effects are responsible for the enhanced toughness recently demonstrated experimentally for cubic single-crystal pseudobinary V0.5 W0.5 N and V0.5 Mo0.5 N epitaxial layers. Graphical abstract: